Land Ownership and Income Distribution of People in Ngimbakan and Mranggen Municipality Polokarto Sub-District, Sukoharjo - Astuti, Wahyuni Apri (Forum Geografi, 1996)
The research is conducted in Ngombakan and Mrangeen, two villagein district of polokarto, Sukoharjo regency. The two villages employe two different irrigation systems, one technical and the other non-technical. The study aims at two major objectives, namely: 1) the relation between the width of agricultural land holding and the income distribution of the different irrigation systems employed in the two villages; and 2) yhe influence of land holding having different irrigation systems on the agricultural income, non agricultural income as well as the household income. The sample include 225 respondents selected in proportion. They consist of 75 respondents that come from the village employing the technial irrigation. And 150 respondents from that employing the non-technical irrigation. The samples are taken in random. The analysis is conducted by means of cross-table analysis, frequency distribution, and product moment correlation.The result of the reasearch show that 1) there is small rate of land holding in two village; 2) there is a great deal of inequalityÂ of land holding in the two villages in which it is higher in Mranggen than that in Ngombakan (Gini index in Mranggen is 0.668, where as that in Ngombakan is 0.602); 3) there is a considerable inequality of agricultural income in which Mranggen is higher than Ngombakan; 4) there is a slight differene of household income in two villages; 5) there is positive correlation between the widht of land holding and the agricultural income, non agricultural income as well as the household income in Mranggen; 6) there is a positive correlation between the widht of land holding and agricultural income but there is no significant correlation between the widht of land holding and the non agricultural income as well as that of the household. The study was found out that the non-agricultural sector is playing an inreasingly important role in the distribution of household income. The inequality of agricultural income in the villages is considerably high but the inequality of the total income as well as that of the income per capita is relatively low. The contribution of the agricultural sector to the total income is lower than that of the non-agricultural. There is a difference of poverty level in which respondents employing the tehnical irrigation have a lower degree of poverty than those employing the non-technical irrigation.